Penerapan Metode Demonstrasi untuk Meningkatkan Hasil Belajar Seni Budaya dan Keterampilan di Kelas IV - Lina Novita (Pedagogia: Jurnal Ilmiah Pendidikan, 2016)
The research was conducted with the approach of Classroom Action Research (CAR). It was done collaboratively within two cycles. The aim of the research is to describe the improvement of the fourth grade students’ achievement on the subjects of cultural art and craft making using the method of demonstration at SDN Sindangsari in the sub-district of Bogor Utara, Bogor, in the first semester, the academic year of 2013/2014. The subjects of the research were the teacher and the students of the fourth grade. There were 32 students consisting of 15 girls and 17 boys. The research result shows that the students’ completion at the first cycle was 53% or only 17 students completed the task given while at the second cycle, there were 25 students completed the task given or it was 78%. In addition, in the observation of the students’ activities, there was an improvement of students’ participation and attitudes from 53.4% whose category is fair at the first cycle to 73% whose category is good at the second cycle. Therefore, it can be inferred that the use of demonstration method is able to improve students’ achievement on the subjects of cultural art and craft making of the fourth grade students at SDN Sindangsari in the sub-district of Bogor Utara, Bogor. Besides that, the research also shows that the method is able to improve students’ behavior on the subjects of cultural art and craft making.